2019
DOI: 10.3168/jds.2018-14953
|View full text |Cite
|
Sign up to set email alerts
|

Acute-phase inter-alpha-trypsin inhibitor heavy chain 4 (ITIH4) levels in serum and milk of cows with subclinical mastitis caused by Streptococcus species and coagulase-negative Staphylococcus species

Abstract: The aim of the study was to investigate the concentrations of acute-phase inter-α-trypsin inhibitor heavy chain 4 (ITIH4) in serum and milk of cows with subclinical mastitis caused by Streptococcus spp. (STR) and coagulase-negative Staphylococcus spp. (CNS) and healthy cows. The blood and milk samples were obtained from 60 mid-lactation, multiparous Holstein-Friesian cows from 7 herds in the Lublin region of Poland. In the milk samples from 40 cows with subclinical mastitis, Streptococcus spp. and CNS were iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…Our previous studies showed that HP dramatically accelerated the progression of AD pathology accompanied with inflammation [25]. In addition, ITIH4 is regulated by IL-6, which regulates inflammation [26][27][28]. In the present study, HP significantly increased the expression of ITIH4 in the CTX, HI, and TH of APP23 mice (Figs.…”
Section: Discussionsupporting
confidence: 69%
“…Our previous studies showed that HP dramatically accelerated the progression of AD pathology accompanied with inflammation [25]. In addition, ITIH4 is regulated by IL-6, which regulates inflammation [26][27][28]. In the present study, HP significantly increased the expression of ITIH4 in the CTX, HI, and TH of APP23 mice (Figs.…”
Section: Discussionsupporting
confidence: 69%
“…ITIH4 may function as an APP for the protection of the uterus from the inflammatory response in pig endometrium [ 17 ]. Furthermore, ITIH4 has also been extensively studied as a biomarker in cancers and other disorders and in other biological contexts [ 24 , 25 , 26 , 27 , 28 ]. Despite the significance of ITIH4 in mammals, research regarding the function of this protein in insects has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, compared with the blank group, the challenge group exhibited significantly upregulated expression of Orm1, Hp and ITIH4 in the mammary gland. In previous studies, ITIH4 was detected in mammary tissue [32,33], serum [34] and milk [35] of dairy cows with mastitis, and the concentration of this protein in these cows was significantly higher than that in healthy dairy cows. ITIH4 is a glycoprotein produced mainly by the liver and secreted into plasma, belonging to the inter alpha trypsin inhibitor (ITI) family [36].…”
Section: First Category Second Category Protein Numbermentioning
confidence: 78%